2007
DOI: 10.1152/ajpheart.00822.2007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in forearm muscle temperature alter renal vascular responses to isometric handgrip

Abstract: The purpose of the present study was to examine the effect of heating and cooling the forearm muscles on renal vascular responses to ischemic isometric handgrip (IHG). It was hypothesized that heating and cooling the forearm would augment and attenuate, respectively, renal vascular responses to IHG. Renal vascular responses to IHG were studied during forearm heating at 39°C ( n = 15, 26 ± 1 yr) and cooling at 26°C ( n = 12, 26 ± 1 yr). For a control trial, subjects performed the experimental protocol while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The main finding of this study was that blood flow modulates the effect of muscle heating on MSNA responses to DHG (study 1). However, consistent with our previous findings using isometric handgrip (12,20), muscle heating augmented MSNA responses during ischemic DHG (study 2).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The main finding of this study was that blood flow modulates the effect of muscle heating on MSNA responses to DHG (study 1). However, consistent with our previous findings using isometric handgrip (12,20), muscle heating augmented MSNA responses during ischemic DHG (study 2).…”
Section: Discussionsupporting
confidence: 93%
“…By occluding blood flow during exercise, we were able to significantly augment exercise-mediated increases in MSNA during muscle heating, and thus confirm our previous results (12,20). Moreover, our results clearly implicate blood flow as a potent modifier of heat-related MSNA responses during dynamic exercise.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, we speculate that the afferent signals from muscle metaboreceptors would augment the activity of thermoregulatory center when this center is already activated by increasing core or skin temperatures. In addition, it has been suggested that an elevation of muscle temperature would augment the responsiveness of muscle afferents (26,39), implying that the elevated muscle temperature associated with passive heating would influence sweating response caused by muscle metaboreceptors in the present study.…”
Section: Discussionmentioning
confidence: 60%